Socialising Tourism Rethinking Tourism for Social and Ecological Justice (Taylor & Francis, 2021)
socialising tourism; social tourism; ecological justice; social justice; values; ethics
English
Keywords: Tourism industry; socialising tourism; social tourism; ecological justice; social justice; values; ethics